Complete chloroplast genome sequences of two Amomum species (Zingiberaceae). Issue 2 (3rd July 2019) - Zhang, Ying-Min; Yang, Cong-Wei; Liu, Ying-Ying; Yang, Yao-Wen; Liu, Xiao-Li; Li, Guo-Dong
Abstract: Amomum tsao-ko and Amomum paratsaoko are well known medicinal and edible plants with a strong fragrance and flavour in China. Here, we have sequenced the two complete chloroplast genomes of Amomum tsao-ko and Amomum paratsaoko, which are 163, 612 bp and 163, 487 bp in length, respectively, and exhibited LSC and SSC regions separated by a pair of inverted repeat regions. The cp genome of A. tsao-ko has 120 annotated genes, including 82 protein-coding genes, while A. paratsaoko has 121 annotated genes, including 83 protein-coding genes. Both cp genomes contained 30 tRNA genes and 8 rRNA genes. Phylogenetic analysis using a total chloroplast genome DNA sequence of 28 species revealed a close relationship between A. tsao-ko and A. paratsaoko with 100% bootstrap value.